Content Analysis of Warning Signs Identified as Part of Crisis Response Planning in a Community Sample of Gun Owners and Non-owners - Bauder, Christina Rose; Hay, Jarrod M.; McClung, James G.; Starkey, Austin G.; Bryan, Craig J. (Frontiers in Psychiatry, 2022)
Background: Assessing for and identifying those at imminent risk for suicide continues to present challenges, especially as many who die do not interact with specialty mental health treatment preceding suicide. Suicide-specific interventions in healthcare settings have been found to improve suicide-related outcomes, yet little is known about the confluence of behavioral, cognitive, emotional, and physiological indicators of emotional distress as they correspond to other key risk characteristics and high-risk groups like gun owners. Aim: The purpose of this content analysis study was to examine differences in self-identified warning signs of distress between gun owners and non-owners through crisis response planning (CRP). Methods: Participants completed a collaborative CRP. Warning signs were categorized as being either behavioral, cognitive, emotional, or physiological in nature. Bivariate logistic regression models were used to examine associations between firearm ownership and variables of interest. Participants were evenly split between men (n=44) and women (n=44) and were predominantly white (67.1%) with a mean age of 35.9 (SD=13.56) Results: Emotional warning signs of distress (68.2%) were reported slightly more often than (behavioral (65.9%) followed by physiological (52.3%) and cognitive (46.6%). Firearm owners were significantly more likely to be male (OR=2.5, 95%CI [1.07-6.0]). All participants were about a fourth as likely to report both a behavioral and physiological warning sign concurrently (OR=0.26, 95%CI [0.09-0.67]). Conclusion: Similarities and departures in warning signs of emotional distress may inform future research exploring both self-reported warning signs and related self-management strategies identified through suicide-specific interventions, particularly among high-risk groups such as gun owners.